A bibliometric analysis of the studies on dental implant failure - Farhan Raza Khan; Syed Murtaza Raza Kazmi; Yusra Fahim Siddiqui (Journal of the Pakistan Medical Association, 2022)
Objective: To identify top 30 studies related to dental implant failures based on bibliometric analysis. Methods: The bibliometric study was conducted at Aga Khan University, Karachi from April 2021 to June 2021 and comprised database search on Google Scholar used key words "dental implant failures" for studies published between 1990 and 2020. The selected studies were reviewed based on citation count for which the cut-off date was June 1, 2021. Results: The top 30 papers on dental implant failures had median citation count of 153 (range: 41-1583. Most of the studies were retrospective 11(36.7%), followed by literature reviews 6(20%). The top three contributing journals were the 'International Journal of Oral Maxillofacial Implants' 6(20%), the 'Clinical Oral Implants Research' 5(16.7%) and 'Clinical Implant Dentistry and Related Research' 3(10%). Goteborg University, Sweden, contributed the maximum number of most cited papers 8(26.7%). Continuous...